An efficient liquid crystalline ionomer β‐nucleating agent featuring π‐π stacking and ionic interactions for isotactic polypropylene. Issue 3 (30th March 2020) - Yang, Rong; Cao, Hongwei; Chen, Weilong; Ding, Lv; Chen, Li; Zhang, Xin; Li, Jinchun
Abstract: Polymeric β‐nucleating agents (β‐NAs) have the advantages of good thermal stability, low toxicity, and relatively superior compatibility with isotactic polypropylene (iPP). However, endowing polymeric β‐NAs with high efficiency remains a challenge. Herein, we report a strategy that incorporates ionic monomers into polymeric β‐NAs to significantly enhance their nucleation efficiency. Sodium dimethyl 5‐sulfonatoisophthalate, an ionic monomer, is introduced into a liquid crystalline polyester NA (PBDPS), and the resulting ionomer is named PBDPSi. The attractive interaction between the ion pairs acts as physical crosslinks and stabilizes the active nucleation center of the ordered benzene rings. Moreover, the ionic monomer modifies the viscosity of the liquid crystalline NA and improves the dispersibility of PBDPSi in the iPP matrix. In addition, it enhances the relative growth rate of β‐spherulites of iPP. When 5% sulfonate monomer is introduced into the NA, PBDPSi exhibits the optimal β‐nucleation effect, and the maximum value (0.97) of the relative content of β‐iPP crystals ( k β ) is obtained. Compared with PBDPS, PBDPSi shows better β‐nucleation performance, especially at low concentrations. The incorporation of 0.1 wt% PBDPSi into iPP provides a k β value of 0.41, which is almost four times that obtained with PBDPS. Abstract : Sodium dimethyl 5‐sulfonatoisophthalate, an ionic monomer, is introduced into a liquid crystalline polyester, and the resulting ionomer is an efficient β‐nucleating agent for isotactic polypropylene (iPP). The attractive interaction between the ion pairs acts as physical crosslinks and stabilizes the active nucleation center of the ordered benzene rings. Moreover, it enhances the relative growth rate of β‐spherulite of iPP. In addition, the maximum value (0.97) of the relative content of β‐iPP crystals can be obtained.